2007
DOI: 10.1540/jsmr.43.201
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the time to maximal [<sup>13</sup>CO<sub>2</sub>] excretion and the half-[<sup>13</sup>CO <sub>2</sub>] excretion time as a gastric emptying parameter: Assessments using the Wagner-Nelson method

Abstract: In the [ 13 C]-octanoate breath test, two popular parameters have been used to quantify gastric emptying rates, namely the time to the maximal [ 13 CO2] excretion (Tmax) and the time to the half-[ 13 CO2] recovery (T1/2b). Although each of Tmax and T1/2b is closely correlated with the scintigraphic half-emptying time, the two parameters occasionally indicate different judgments on a gastric emptying rate. In this study, to clarify which of the two parameters is more reliable, Tmax and T1/2b were compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 16 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…emptying time is expressed as (-1/k)ln(1 -2 -1/β ){ln(β)}/k and the lag phase as (-1/k)ln(1 -2 -1/β ). (Takahashi et al, 2006;Sanaka et al, 2007b;Sanaka et al, 2008;Iwase et al, 2009;Shindo et al, 2009;Mishima et al, 2009). In this context, Tlag is replaced by Tmax afterward in the present review.…”
Section: Interpretation Of Breath-test Parametersmentioning
confidence: 87%
See 3 more Smart Citations
“…emptying time is expressed as (-1/k)ln(1 -2 -1/β ){ln(β)}/k and the lag phase as (-1/k)ln(1 -2 -1/β ). (Takahashi et al, 2006;Sanaka et al, 2007b;Sanaka et al, 2008;Iwase et al, 2009;Shindo et al, 2009;Mishima et al, 2009). In this context, Tlag is replaced by Tmax afterward in the present review.…”
Section: Interpretation Of Breath-test Parametersmentioning
confidence: 87%
“…This finding is quite understandable, considering that the CPDR[t] curve changes minimally while the PDR[t] curve does dynamically in the early phase (Zai et al, 2009). Next, T1/2b would be prone to mistakenly judge a "normal" emptying to be "delayed" in case that the PDR[t] curve exhibits a very gentle descending slope Shishido et al, 2002;Lee et al, 2000;Sanaka et al, 2007b); in such a case, we speculates that the retention, rather than a real delay in the emptying, makes the pulmonary […”
Section: And the Cpr [T] Curve (The Velocity) Is Flattened Without A mentioning
confidence: 99%
See 2 more Smart Citations
“…Further studies will be warranted to determine whether the early phase of gastric emptying such as AUC 5 value was associated with pancreatic enzyme abnormalities in FD patients. In addition, previous studies have reported that solid test meals [43] and liquid meals [44][45][46] were used for assessment of the early phase of gastric emptying. In the future, we have to compare the early phase of gastric emptying evaluated by solid test meals with liquid test meals.…”
Section: Discussionmentioning
confidence: 99%